What ails Indian bureaucracy - Bandyopadhyay, D. (2001)
In this paper, Shri D. Bandyopadhyay pens his reminiscences as an `unrepentant bureaucrat of thirty-five years vintage'. In a democratic polity, power belonged to the people and it was to be exercised by their representative. Civil servants in the executive branch could only be given delegated authority. They could, of course give their professional advise to the political executive. Civil servants were expected to discharge their duties, without fear or favour affection or ill will. Unfortunately, deviation from these principles appeared to be the norm rather than the exception. - Reproduced.
Keywords: Bureaucracy - India; Bureaucracy